The Tendency of Having MSH2 and MSH6 Microsatellite Instability among Clinicopathological Features in Patients with Colorectal Cancer - Arshita, Neni (Asian Pac J Cancer Prev, 2018)
OBJECTIVE: This study aimed to identify micro-satellite instability (MSI) based on the expression of MMRp (MSH2 and MSH6) and to evaluate the association of MSI and with clinicopathological features in patients with colorectal cancer (CRC). METHODS: MMRp expression in 80 tissue samples from patients with adenocarcinoma CRC were evaluated by using anti-MSH2 and -MSH6 antibodies. Loss of MSH2 and/or MSH6 expression was stated as MSI. The association between MSI status and clinicopathological features were analyzed by using binary logistic regression (p<0.05). RESULTS: The frequency of MSI in patients with CRC varied, corresponding to 8.3% (6/72) MSH2 MSI, 36.1% (26/72) MSH6 MSI and 6.9% (5/72) MSH2-MSH6 MSI. Male patients (OR=1.98), with tumor located in colon (OR=1.47) and late stage tumor (OR=1.48) have a tendency of having MSH2 MSI. Male patients (OR=1.4), with tumor located in colon (OR=2.53) and poor tumor differentiation (OR=3.02) have a tendency to encounter MSH6 MSI. Male patients (OR=4.93) with late stage tumor (OR=1.69) have a tendency of having MSH2-MSH6 MSI. CONCLUSION: Patients more likely to have MSH2 MSI are males, and/or having tumor located in colon, and /or having late stage tumor. Patients more likely to have MSH6 MSI are males, and/or having tumor located in colon, and/or having tumor with poor differentiation. Patients who have greater tendency to have MSH2 and MSH6 MSI are males, and/or having late stage tumor.